What if simulation for a Brazilian company regarding marketing budget - PINTO, Diogo André (Journal of Economic Development, Environment and People, 2016)
The article research is a case study regarding how to design the marketing budget for a small Brazilian company that started the activity one year ago. Taking into account the data that we gather, we decided to use What-if simulation. The case study is a simplified model representation of a company, adjusted according to the data that is released as target for the following year. In practice, the formulation of a scenario allows the construction of a hypothetical world that the analyst can see and navigate.